Tracing the Evolution of Contemporary French Studies Through the Twentieth (and Twenty-first) Century French (and Francophone) (Literary) Studies Colloquium. Issue 3 (26th May 2016) - Willging, Jennifer
ABSTRACT: This essay takes the call of the 2015 Twentieth (and Twenty-first) Century French (and Francophone) (Literary) Studies Colloquium to "trace the evolution of French and Francophone Literary Studies" quite literally in that it compares a sampling of programs over the colloquium's thirty-two-year history in order to analyze some of the signs of change in the field over this period. While the Colloquium is only one gauge of the multiple mutations that have occurred in French Studies over the last three decades, a reading of the shifts in the texts, topics, artists, geographical regions, and critical approaches treated at it, as well as in the types of scholars who have participated in it, can certainly tell us something about the ways in which the meaning of the evolving signifier "Twentieth (and Twenty-first) Century French (and Francophone) (Literary) Studies" has changed over time.